The Impact of Islamic-Based Career Information Service to Improve Students Career Aspirations: Array - Paramita Nuraini; Tawil Tawil; Subiyanto Subiyanto (Islamic Guidance and Counseling Journal, 2019)
This study was based on the low career aspirations of the students' at senior high school of Muhammadiyah 1 Magelang, Indonesia and the lack of Islamic approach to improving career aspirations. Many students who did not have a career goal after graduating from high school. Otherwise, guidance and Counseling Teachers still use conventional career information services. The aim of this study is to determine the effectiveness of information services based on Islamic approach in improving career aspirations of students at Senior High School of Muhammadiyah 1 Magelang. The type of this research was quasi-experiment research with pretest design and posttest group design. The student population of the tenth class was 240 students, and the sample (purposive sampling) was 30 students. Data collecting tool in this research was the career aspirations of the student. The result of this research showed there was an improvement of the career aspirations of the student after receiving a career information service based on Islam intervention. This result indicated that career information service based on Islam is effective in improving student career aspirations.